Renal cell carcinoma associated with peritumoral sarcoid-like reaction without intratumoral granuloma - Ouellet Simon; Albadine Roula; Sabbagh Robert (Diagnostic Pathology, 2012)
Abstract Non-necrotizing epithelioid granulomas have been described in association with many primary tumors. In such cases, they are designated as sarcoid-like reaction. Although it is more seen in carcinomas than in sarcomas, it is very rarely reported in renal carcinoma. Here, we describe a rare association of prominent peritumoral sarcoid-like reaction without intratumoral granulomas and conventional clear cell renal carcinoma in a 62-year-old-male, without clinical or laboratory finding of sarcoidosis. At 30 months follow-up, he had no recurrence. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/4054525336657922